2017
DOI: 10.4172/2161-0495.1000335
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol Intoxication in an 8-Months-Old Infant through Breastfeeding: A Case Report

Abstract: Tramadol is a widely used, synthetic centrally acting opioid analgesic commonly used for the treatment of moderate to severe pain. Very few reports about its excretion into breast milk were published and most of them suggested that short-term maternal use of tramadol is compatible with breastfeeding. No available data about its chronic daily use in addict lactating mothers. To date, there are no published reports of tramadol poisoning through breastfeeding. We report a case of tramadol intoxication in 8-month-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Tramadol is not recommended for use during breastfeeding. There has been a case report on the death of an 8-month-old breastfed infant from tramadol; however, the case cannot be attributed to breast milk exposure alone, as the sudden onset of symptoms at 8 months of age seems implausible . Other studies have found no adverse effects attributable to tramadol with standard maternal dosages …”
Section: Discussion and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tramadol is not recommended for use during breastfeeding. There has been a case report on the death of an 8-month-old breastfed infant from tramadol; however, the case cannot be attributed to breast milk exposure alone, as the sudden onset of symptoms at 8 months of age seems implausible . Other studies have found no adverse effects attributable to tramadol with standard maternal dosages …”
Section: Discussion and Observationsmentioning
confidence: 99%
“…There has been a case report on the death of an 8-month-old breastfed infant from tramadol; however, the case cannot be attributed to breast milk exposure alone, as the sudden onset of symptoms at 8 months of age seems implausible. 32 Other studies have found no adverse effects attributable to tramadol with standard maternal dosages. [33][34][35] Codeine and oxycodone are not recommended to be used during breastfeeding, and other narcotics are preferred.…”
Section: Drug Considerations Analgesicsmentioning
confidence: 95%
“…LactMed states that the excretion of tramadol into milk is low and even lower amounts of the active metabolite, O-desmethyltramadol, are excreted and a study of breastfeeding in newborn infants found no adverse effects attributable to tramadol compared with controls [20]. There has been one death, however, in the 8-month-old breastfed infant of a woman addicted to tramadol, although the death was not definitely attributable to tramadol exposure in breastmilk [29]. Current RCOG advice states that tramadol can continue to be used (with caution) during breastfeeding and the lowest effective dose should be used for the shortest time possible [19].…”
Section: Tramadolmentioning
confidence: 99%
“…Recommendations were based on a systematic review [16] (including a large prospective cohort study of over 1.6 million women [27]), UKTIS [18] (including case reports [28]), LactMed [20] (including [29]) and RCOG guidance [19], as shown in Supplementary Table S3, available at Rheumatology online.…”
Section: Tramadolmentioning
confidence: 99%